2016
DOI: 10.1021/acschemneuro.6b00417
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin in Space: Understanding Single Fibers

Abstract: All brain regions contain fibers that store and release 5-hydroxytryptamine (5-HT, serotonin). Since these fibers often do not have well-defined trajectories, most studies have focused on their overall densities, a measure that can be associated with local 5-HT tone in heathy and diseased brains. However, the observed fiber densities are the consequence of the behavior of single fibers. Evidence is presented as to why understanding single-fiber trajectories is important for basic and clinical neuroscience. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…If fibers are not static and continue to grow in the adult brain, it raises a natural question: What processes allow achieving a steady equilibrium of densities? We have previously suggested that in the healthy brain serotonergic fibers may be routinely interrupted and that these interruptions may be associated with microglia . By using super-resolution microscopy (STED), we now have obtained evidence consistent with this hypothesis (Figure C).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…If fibers are not static and continue to grow in the adult brain, it raises a natural question: What processes allow achieving a steady equilibrium of densities? We have previously suggested that in the healthy brain serotonergic fibers may be routinely interrupted and that these interruptions may be associated with microglia . By using super-resolution microscopy (STED), we now have obtained evidence consistent with this hypothesis (Figure C).…”
supporting
confidence: 75%
“…We have previously suggested that in the healthy brain serotonergic fibers may be routinely interrupted and that these interruptions may be associated with microglia. 2 By using super-resolution microscopy (STED), we now have obtained evidence consistent with this hypothesis (Figure 2C). We note that this finding should not be generalized without more extensive studies.…”
Section: Acs Chemical Neurosciencesupporting
confidence: 65%
See 1 more Smart Citation
“…In this study, 5-HT-immunoreactive fibers are most concentrated in the area within the NTS defined as the dorsomedial region (Phifer and Berthoud, 1998; Pool et al, 2007; Zheng et al, 1999). In serotonergic fibers, 5-HT is concentrated in specialized varicosities with variable dimensions (Bjarkam et al, 2003; Janušonis, 2017; Ruda et al, 1982). In the current study, a 15-min exposure to FPL64176 resulted in a moderate enhancement of 5-HT immunoreactivity within the dorsomedial subdivision of the NTS, marked by numerous varicosities of varying sizes, suggesting subdivision-specific response to administration of FPL64176.…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that there are around 6 × 10 6 varicosities/mm 3 in the rat cortex. In addition, each cortical neuron may receive around 200 varicosities ( 94 , 95 ). However, there is evidence of some non-5-HT producing neurons that transiently express 5-HTT during development in the thalamus identified by 5-HT uptake and in situ hybridization for 5-HTT RNA ( 96 ).…”
Section: Visualizing Serotonin Axonsmentioning
confidence: 99%